2007
DOI: 10.1007/s11239-007-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high altitude and sea level on mean platelet volume and platelet count in patients with acute coronary syndrome

Abstract: A relationship exists between exposure to high altitude and increased coagulability. Mean platelet volume is a parameter of platelet functions and may be a marker for increased platelet aggregability. The aim of this study was to compare the mean platelet volumes and platelet counts in patients who experienced an acute coronary event at moderately high altitude and at sea altitude. Four hundred and one patients who experienced an acute coronary event were enrolled, of them 211 were born and had been living at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Furthermore, Sharma found there was no significant difference in PLT counts when 50 subjects were moved from low altitude to 3650 m [29]. These results may be explained by the fact that PLT function may be influenced by physiological changes that occur during adaptation to HA, such as increase of aggregation and adhesion of PLT, but not PLT count [19,21,30]. In addition, the factors which can affect the functions of RBC and PLT, such as 2,3-diphosphoglycerate (2,3-DPG) can facilitate O 2 release from hemoglobin, meanwhile, 2,3-DPG inhibits PLT aggregation, but it not change HGB concentration, HCT, and count of PLT [21,31].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Sharma found there was no significant difference in PLT counts when 50 subjects were moved from low altitude to 3650 m [29]. These results may be explained by the fact that PLT function may be influenced by physiological changes that occur during adaptation to HA, such as increase of aggregation and adhesion of PLT, but not PLT count [19,21,30]. In addition, the factors which can affect the functions of RBC and PLT, such as 2,3-diphosphoglycerate (2,3-DPG) can facilitate O 2 release from hemoglobin, meanwhile, 2,3-DPG inhibits PLT aggregation, but it not change HGB concentration, HCT, and count of PLT [21,31].…”
Section: Discussionmentioning
confidence: 92%
“…This systemic inflammatory state promotes megakaryocytes (especially interleukin 3 and 6) to produce platelets (15). An increase in MPV is seen, which indicates that thrombocytes that are both metabolically and enzymatically more active than smaller ones, because large thrombocytes have more dense granules containing more thromboxane A2 (3,4). However, MPV is not paid enough attention by most clinicians; determination of MPV is a cheap, readily available, and reliable method of assessing platelet functions and is automatically calculated by hematology analyzers.…”
Section: Discussionmentioning
confidence: 99%
“…Larger platelets have more thromboxane A2-containing dense granules, which are associated with higher activity (3,4). Increased MPV is associated with a variety of conditions and diseases such as smoking, diabetes, ischemic coronary diseases, and thromboembolism.…”
Section: Introductionmentioning
confidence: 99%
“…At approximately 4,400 feet above sea level, Northern Nevada, where this study is conducted, is considered a high desert in the Sierra Nevada foothills. Alper showed that mean platelet volume (MPV) is 7.5% higher at altitudes greater than 4,000 feet than at sea level [14]. Similarly, Hudson showed a notable and statistically significant positive correlation with platelet counts (PC) and altitude [15], while mean corpuscular volume (MCV) was recorded as lower at higher altitudes than at sea level [16].…”
Section: Introductionmentioning
confidence: 99%